Characteristics of men who have sex with men and transgender women in Myanmar who test frequently for HIV. (2018) - Veronese, Vanessa; Oo, Zaw Min; Thein, Zaw Win; Draper, Bridget; Aung, Poe Poe; Ryan, Claire; Thant, Myo; Hughes, Chad; Stoové, Mark
No abstract available